Analysis of the Efficacy of LNSRH Surgery for Early Cervical Cancer Based on T, B, and NK Lymphocytes - Lijie He; Liangliang Ma; Heping Zhang (IMR Press, 2023)
Background: The analysis is based on the level of T, B, NK lymphocytes to evaluate the efficacy of laparoscopic nerve-sparing radical hysterectomy (LNSRH) for early cervical cancer. Methods: Selected 30 patients with early cervical cancer who underwent LNSRH surgery in Tianjin Fifth Central Hospital from December 2019 to January 2021 as the cervical cancer group, and 30 healthy female who underwent physical examination in our hospital during the same period were selected as the control group. The expressions of CD4+, CD8+, CD20+, and CD57+ were detected by flow cytometer, female sexual function index (FSFI) and overall assessment scale of cancer treatment function (FACT-G) score were used to evaluate female sexual function and quality of life, and the receiver operating characteristic curve (ROC) was used to analyze the expression predictive value of CD4+, CD8+, CD20+, and CD57+ in LNSRH of early cervical cancer. Results: The expression of CD4+ and CD57+ in the cervical cancer group was lower than that in the healthy group,and the expression of CD8+ and CD20+ was higher than that in the healthy group (p < 0.05). The expression of preoperative CD4+ and CD57+ was higher for postoperative, and the expression of preoperative CD8+ and CD20+ was lower (p < 0.05) for postoperative. The expression of postoperative 1 day CD4+ and CD57+ was higher for at 3 days postoperative, and the expression of postoperative 1 day CD8+ and CD20+ was lower at 3 days postoperative (p < 0.05). CD4+, CD57+ expression was positively correlated with FSFI score, and CD8+, and CD20+ expression was negatively correlated with FSFI score, CD4+, and CD57+ expression was positively correlated with FACT-G score, and CD8+, and CD20+ expression was negatively correlated with FACT-G score (p < 0.05). ROC analysis of CD4+, CD8+, CD20+, CD57+ expression sensitivity was lower than the four-item combination, the specificity was higher than the four-item combination and the results with significant statistical difference (p < 0.05) and the four combined tests have good predictive value for the efficacy of LNSRH for early cervical cancer (p < 0.05). Conclusions: Cervical cancer patients were mainly cellular immunity and performed low expression of CD4+, high expression of CD8+, high expression of CD20+, and low expression of CD57+. T, B, and NK lymphocytes could be used for immunological detection of cervical cancer.